The Influence of Kinesio Taping on the Effects of Physiotherapy in Patients after Laparoscopic Cholecystectomy - Marcin Krajczy; Katarzyna Bogacz; Jacek Luniewski; Jan Szczegielniak (The Scientific World Journal)
Physiotherapy in patients after laparoscopic cholecystectomy (CHL) is impeded by postoperative pain which causes a decline in patients’ activity, reduces respiratory muscles’ function, and affects patients’ ability to look after themselves. The objective of this work was to assess the influence of Kinesio Taping (KT) on pain level and the increase in effort tolerance in patients after CHL. The research included 63 patients after CHL. Test group and control group included randomly selected volunteers. Control group consisted of 32 patients (26 females, 6 males), test group consisted of 31 patients (22 females, 9 males). Both groups were subjected to complex physiotherapy, and control group had additional KT applications. Before surgery, during and after physiotherapy, patients were given the following tests: 100-meter walk tests, subjective pain perception assessment, and pain relief medicines intake level assessment. The level of statistical significance for all tests was established at 𝑃<0.05. Statistical analysis showed a significant decrease in the time required to cover a 100-meter distance and a decrease in pain perception presented by significantly lower painkillers' intake in the test group in comparison with the control group. The improvement in clinical condition observed in the research indicates the efficiency of KT as a method complementing physiotherapy in patients after laparoscopic cholecystectomy.